Influence of Brand Loyalty on Fast Food Industry - Consumer buying behavior of India. - Tandon, Manav (2012)
The purpose of this research is to examine how consumers are influenced by factors of brand loyalty towards fast food brands. The research was conducted in Delhi with Indian consumers. People who filled the questionnaire are adults who are working or are looking for job. This research was adopted based on seven factor of brand loyalty. The seven factors of brand loyalty are brand name, product quality, price, style, promotion, and service quality and restaurant environment. Brand name has shown strong correlation with brand loyalty. In order to increase customer satisfaction and drive them to be brand loyalists, marketers are encouraged to develop aggressive marketing programs. The questionnaire was loaded on surveymonkey.com website and people were contacted personally via email, SMSs and phones to fill the questionnaire. Questionnaire was self-administered to all respondents and finally 107 respondents gave complete responses. Frequency, Cross-tabulation and Reliability and Validity test are part of study. The research results showed that there is positive and significant relationship between factors of brand loyalty (brand name, product quality, price, style, promotion, and service quality and restaurant environment) with fast food restaurants and brand loyalty. Study of more focused factors that are appropriate to the Indian environment is recommended in order to obtain accurate information. Keywords: Brand loyalty, Fast food industry, Indian consumers, McDonald, Haldiram’s